Bedside Manners : Play and Workbook - SUZANNE GORDON, LISA HAYES (Cornell University Press, 2013)
This play and workbook are about teamwork and communication, which are, of course, at the heart of any theatrical performance. We would, therefore, like to recognize the team that has produced this book. We acknowledge, primarily, the considerable eff ort that went into our work with one another. First came an idea, then a dual collaboration, and fi nally, a triad. We also acknowledge Fran Benson, editor of the ILR Press at Cornell University Press, for taking the leap to transform this project from a play delivered by the Internet or individually printed copy to a published book. Ditto to everyone else at Cornell for believing in this project—Mahinder Kingra, Jonathan Hall, Nathan Gemingnani, Ange Romeo-Hall, and last but defi nitely not least John Ackerman and Peter Potter. We also thank Kitty Liu for all her patience and assistance.